Neuronal Rat Brain Damage Caused by Endogenous and Exogenous Hyperthermia - Aydin, Mustafa; Kislal, Fatih Mehmet; Demirol, Mustafa; Girgin, Feyza Incekoy; Kabakus, Nimet; Kocak, Mesut (Turkish Neurological Soc, 2012)
Objective: Hyperthermia may induce pathologic alterations within body systems and organs including brain. In this study, neuronal effects of endogenous and exogenous hyperthermia (41 degrees C) were studied in rats. Material and Method: The endogenous hyperthermia (41 degrees C) was induced by lipopolysaccharide and the exogenous by an (electric) heater. Possible neuronal damage was evaluated by examining healthy, apoptotic and necrotic cells, and heat shock proteins (HSP 27, HSP 70) in the cerebral cortex, cerebellum and hypothalamus. Results: At cellular level, when all neuronal tissues are taken into account; (i) a significant increase in the necrotic cells was observed in the both groups (p<0.05), (ii) while exogenous hyperthermia did not affect apoptotic process significantly, endogenous hyperthermia led to a significant increase in apoptosis (p<0.05), whereas (iii) HSP 70 levels increased in neuronal tissues (p<0.05) in the endogenous hyperthermia group, but they decreased in the exogenous hyperthermia group (p<0.05). No statistically significant change was observed in HSP 27 levels in both of the groups (p>0.05). Discussion: The neural tissue of brain can show different degree of response to hyperthermia. But we can conclude that endogenous hyperthermia is more harmful to central nervous system than exogenous hyperthermia.
Ratlarda endojen ve eksojen hiperterminin sebep oldu?u noronal beyin hasarı
Keywords: Hyperthermia; rat; brain damage